(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper gives a global vision of the Iberian epigraphy attested in Tarraco; in particular it takes into account the false inscriptions from the 19th century, since they are one of the main difficulties in order to establish the final corpus. In the present contribution we propose that some inscriptions usually considered as genuine should be excluded from the corpus, while others, which had been rejected, could be reconsidered as authentic. The second part of the article introduces the analysis of the lost epigraphs, some of them being exclusively transmitted by manuscript tradition, and, finally, a new group of graffiti on pottery is assessed.